Particle swarm optimization tuned controllers for capacitor voltage balancing and harmonic suppression in modular multilevel converters - Outazkrit, Mbarek; aamri, Faicel El; Jaoide, Essaid; Radouane, Abdelhadi; Mouhsen, Azeddine (International Journal of Electrical and Computer Engineering (IJECE), 2025)
The modular multilevel converter (MMC) has become a highly attractive power converter topology for various applications due to its modularity and scalability. However, it faces significant challenges, such as capacitor voltage balancing and circulating current, which can lead to instability and high-power losses. While the sorting algorithm is commonly used to balance capacitor voltages, this paper uses an individual balancing control method as an alternative. Additionally, a proportional resonant controller is employed to suppress the second and fourth harmonics in the circulating current. This paper presents a method for tuning the parameters of both the circulating current controller and the individual balancing control using the particle swarm optimization (PSO) algorithm, which represents the main contribution of this work. The MMC system, connected to a grid with a low number of submodules, is modeled and evaluated using the PLECS and MATLAB/Simulink environments. The results demonstrate the effectiveness of the proposed PSO-based tuning method in improving the performance and stability of the MMC.